Gastrointestinal Pathobionts in Pediatric Crohn’s Disease Patients - Rachel V. Purcell; Nadeem O. Kaakoush; Hazel M. Mitchell; John F. Pearson; Jacqueline I. Keenan (International Journal of Microbiology)
Crohn’s disease (CD) is an inflammatory disease of the gastrointestinal tract, with a rising incidence worldwide, particularly in children. CD is thought to arise due to an immune response to environmental factors. The role of bacteria in CD has recently been highlighted, and here, we examine the prevalence of two bacterial species, enterotoxigenic Bacteroides fragilis (ETBF) and Fusobacterium nucleatum, implicated in gastrointestinal pathologies, in a pediatric CD cohort. Stool samples from 30 children with treatment-naïve CD and 30 age- and sex-matched controls were collected, and DNA was extracted. Quantitative PCR was used to determine the levels of ETBF and F. nucleatum in stool samples. Bacterial positivity and relative abundance were assessed between cases and controls and in relation to disease severity. No associations were found between colonization with ETBF and CD, or between colonization with either ETBF or F. nucleatum and disease severity or presence of C. concisus. However, a strong association was observed between positivity for F. nucleatum in the stool samples and the occurrence of CD in patients (25/30) as compared to controls (8/30) (P=0.003). F. nucleatum is more prevalent in the stool samples of pediatric CD patients, compared to healthy controls, and may have potential use as a biomarker of pediatric CD.